Incorporação de lodo de esgoto na massa cerâmica para fabricação de tijolos maciços: uma alternativa para a disposição final de resíduo - Duarte, Anaxsandra da Costa Lima (2008)
The disposal of sewage sludge is a growing problem face up to management of sanitary sevices. Otherwise, because its making process characteristic, the Ceramic Industry can tolerate the presence of this wastes as raw material. This study has as object to confirm the use of the sewage sluge in the Ceramic Industry like a sustentable alternative for its disposal. Futhermore, this study quests to evaluate the maximum proportion for incorporation of sludge wich result in technically and enviromentally suitable bricks. For found this proportion, the research consisted of (1) making of bricks in full scale, adde up 0%, 5%,10%, 15%, 20%, 25%,30%, 35% e 40% sludge, with size 220x105x45 mm, hand-molded by rammer and baked by industrial kiln; and (2) tecnical and enviromental evaluation of this bricks, according to Brazilian norms. The raw material uses were two distinct clays come from Goianinha/RN and sewage comes from a septic system tank and pumped into tank vehicle, of Natal/RN. The technical evaluation allowed to conclude the addiotion of the sludge brings about signifcant lost of mass and the water absorption grew up according to increase of sludge: every sludge-amended clay bricks absorved more water than control group. Thus, the compressive strength was signicantly decreased because the increase of sludge: bricks with 5% sludge added lost 45% of strength achieved at control group; the bricks made with 10 and 20% lost almost 70% of bigger strength. With up to 25% sludge added to the bricks, the streght decreased over 90%. Concerning heavy metal leaching, the two maximum proportion wich have tecnical approval, it means bricks sludge added with 15 and 20%, can say there is no risk of enviromental contamination using those bricks. This way, in this work context, it can to conclude the maximum proportion atends the technical and enviromental criterion is 20%